The Role of Malay Cultural Values in Shaping Character: A Study of Politeness and Courtesy in Family Education - Uri, Fatimah; Jarir, Jarir; Erlina, Gusti (Hikmah, 2025)
The values of politeness and courtesy in Malay culture are increasingly being eroded in the era of globalization, particularly among younger generations. The expressions polite in speech, courteous in action represent moral teachings that have been passed down through generations in Malay families as part of character education. This study explores how these values are instilled within Malay families and their role in shaping individual personality. Using a qualitative approach based on literature review, this research examines oral traditions, customs, and daily practices in Malay households that emphasize ethical communication and respectful behavior toward others. The findings reveal that expressions of politeness in speech and courteous conduct reflect the character education embedded in Malay family life, which cultivates manners, respect, empathy, and wisdom through daily habits and exemplary behavior. These values serve as a cultural identity foundation that must be preserved by the younger generation in modern times. The implications of this study reinforce Ki Hadjar Dewantara’s perspective that the family is the first and foremost educational environment in shaping character. Therefore, the revitalization of local cultural values within family education is essential to strengthen cultural identity and safeguard the younger generation from a moral crisis amid the forces of modernization.